2022
DOI: 10.3389/fmicb.2022.763169
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Genomic Analysis Reiterates Mild Symptoms Post-vaccination Breakthrough: Should We Focus on Low-Frequency Mutations?

Abstract: Vaccine development against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been of primary importance to contain the ongoing global pandemic. However, studies have demonstrated that vaccine effectiveness is reduced and the immune response is evaded by variants of concern (VOCs), which include Alpha, Beta, Delta, and, the most recent, Omicron. Subsequently, several vaccine breakthrough (VBT) infections have been reported among healthcare workers (HCWs) due to their prolonged exposure to viruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The remaining 460 episodes, across 433 individuals, were then analysed (Table 1). These individuals had the same age distribution (median 39 years [IQR 31 -49], as the whole Legacy study (40 years [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]), and were gender matched to Legacy (68 vs 68% female). Symptom questionnaires were completed for 432/460 episodes (94%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 460 episodes, across 433 individuals, were then analysed (Table 1). These individuals had the same age distribution (median 39 years [IQR 31 -49], as the whole Legacy study (40 years [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]), and were gender matched to Legacy (68 vs 68% female). Symptom questionnaires were completed for 432/460 episodes (94%).…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to emphasise that given the observational nature of our study, the sequential spread of Omicron BA.1 and BA.2 in the United Kingdom, and the rapid expansion of third-dose vaccination in December 2021, it was not possible to determine whether differences we observed between Delta and the BA.1 and BA.2 VOCs were attributable to intrinsic differences between these variants, or waning of immune protection afforded by vaccination. The reported shift in COVID-19 symptoms between Delta and Omicron sub-variants may be driven by intrinsic differences in the biology of the virus itself, leading to modified host responses; mutations in the Spike protein of SARS-CoV-2 VOCs may directly impact on symptom profiles through changes in viral tropism (2, 3, 32, 33), However, detailed data on differences in the host response to different VOC in vaccinated, non-hospitalised adults are currently lacking, but are likely to involve an interplay between localised mucosal innate and early T-cell interferon-mediated systemic responses (2, 34, 35). Further studies to determine the mechanisms by which different and emerging VOCs affect the host response are urgently required, and will be a necessary counterpart to clinical studies in the assessment of future VOCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chandramani et al demonstrated that fully vaccinated individuals from an eastern state of India were less likely to develop severe disease [1]. As much as vaccination reduces COVID 19 hospitalizations, there have been significant number of 'breakthrough' infections worldwide, including India, after double dose vaccination, thus allowing the chance of subsequent transmission [2] [3]. Consequently, it is imperative to understand why a subset of patients acquire infection/s after administration of vaccine doses?…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many different VOCs emerged from different parts of the world - Beta (South Africa), Gamma (Japan) and Delta (India). Many VOCs caused a fresh round of infections and mortality, putting further strain on public healthcare infrastructure and medical support ( Kanakan et al 2022 ). India also experienced waves of enhanced COVID-19 infections, the first wave between March 2020-Sept 2020 and the second one from March 2021-June 2021 (Kar et al 2021).…”
Section: Introductionmentioning
confidence: 99%